Institutional Repository Access Policy: A Case Study in State University of Malang Library - Ernaningsih, Dwi Novita (Record and Library Journal, 2017)
This article discusses about access policy to institutional repository in State University of Malang Library. This study aims to analize access policy and accessibility to institutional repository, barriers to adoption of open access, as well as the views of stakeholders to open access institutional repository. The method used is the case study method with qualitative approach. Data was collected by observation, interviews, and document analysis. The result shows that the resistance and disagreement among the stakeholders toward open access institutional repository affect the access policy and accessibility to institutional repository. In protecting academic work, access restrictions which is explicitly does not have legality is applied. The access restriction affects users and visibility of institution. It generates complaints from library users most of whom are digital generation. The restriction also declines the university rank in Webometrics.